Analysis of lead (Pb) levels in community dug well water - Zakiyah Aulia Haruniati; Neneng Nurhayati; Suci Rizki Nurul Aeni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Most lead concentrations in the environment come from human activities. Mining activities have negative impacts on the environment, one of which is exposure to heavy metals such as lead (Pb). The hazards of lead to the human body can cause disorders of the hemopoietic system such as anemia, central and peripheral nervous system disorders, kidney damage, gastrointestinal disorders such as colic and constipation, cardiovascular system disorders, and dysfunction of the adrenal and thyroid glands. Purpose: To measure the concentration of lead metal (Pb) in dug well water. Method: This study used a descriptive method. Samples of dug well water from 14 locations in the area around PT Gunung Bumi Perkasa, Sukabumi Regency were collected using the Simple Random Sampling technique. The samples were then analyzed to determine the level of lead contained using Atomic Absorption Spectrophotometry (AAS) at a wavelength of 217.0 nm. Results: The measurement results showed that the lead levels in the water ranged from 0.0004 to 0.0189 mg/L. Based on these data, all samples still met the quality standards for lead (Pb) levels in clean water, as regulated in Permenkes No.32 of 2017 concerning Clean Water Quality Standards, which is 0.05 mg/L. Conclusion: All 14 samples of dug well water, contained lead below the threshold value for clean water quality.